Respuesta :
Function: h(x) = 2 ^ (-x)
In the table below is the complete calculation of the rate of change.
The last column has the resulting rate of chages for each interval.
Interval change of h(x) change of x rate of change
-2 ≤ x ≤ 0 2^0 - 2^(-(-2)) = -3 0 - (-2) = 2 - 3 / 2 = - 1.5000
0 ≤ x ≤ 2 2^(-2) - 2^0 = - 0.75 2 - 0 = 2 -0.75 / 2 = - 0.3750
-1 ≤ x ≤ 0 2^0 - 2(-(-1)) = - 1 0 - (-1) = 1 -1/1 = -1.0000
0 ≤ x ≤ 1 2^(-1) - 2^0 = - 0.5 1 - 0 = 1 -0.5 / 1 = -0.5000
-2 ≤ x ≤ -1 2^(-(-1)) - 2^(-(-2)) = -2 -1 - (-2) = 1 -2 / 1 = -2.0000
-2 ≤ x ≤ 2 2^(-2) - 2^(-(-2)) = -3.75 2 - (-2) = 4 -3.75/4 = -0.9375
In the table below is the complete calculation of the rate of change.
The last column has the resulting rate of chages for each interval.
Interval change of h(x) change of x rate of change
-2 ≤ x ≤ 0 2^0 - 2^(-(-2)) = -3 0 - (-2) = 2 - 3 / 2 = - 1.5000
0 ≤ x ≤ 2 2^(-2) - 2^0 = - 0.75 2 - 0 = 2 -0.75 / 2 = - 0.3750
-1 ≤ x ≤ 0 2^0 - 2(-(-1)) = - 1 0 - (-1) = 1 -1/1 = -1.0000
0 ≤ x ≤ 1 2^(-1) - 2^0 = - 0.5 1 - 0 = 1 -0.5 / 1 = -0.5000
-2 ≤ x ≤ -1 2^(-(-1)) - 2^(-(-2)) = -2 -1 - (-2) = 1 -2 / 1 = -2.0000
-2 ≤ x ≤ 2 2^(-2) - 2^(-(-2)) = -3.75 2 - (-2) = 4 -3.75/4 = -0.9375
To simplify the other user's answer (which is correct):
1 = D
2 = C
3 = E
4 = F
5 = A
6 = B
Alternatively, your right boxes should look like:
5
6
2
1
3
4